P-035 YI Differences in Colitis Phenotype and Dysplasia Among Patients with Ulcerative Colitis with and Without Primary Sclerosing Cholangitis. (March 2016) - Christophi, George; Li, Ellen; Newberry, Rodney; Davidson, Nicholas; Crippin, Jeffrey; Dassopoulos, Themistocles
Abstract : Background: Patients with ulcerative colitis (UC) and primary sclerosis cholangitis (PSC) exhibit a distinct colitis phenotype compared to UC patients without PSC. Previous studies suggested that UC + PSC patients have milder colitis but higher rates of colorectal neoplasia than UC patients without PSC. We conducted a large, case-control, tertiary center study to characterize the clinical and pathological features of colitis in UC + PSC versus UC patients. Methods: We reviewed consecutive evaluations at the Washington University School of Medicine gastroenterology clinic between 1996 and 2014. 968 UC and 328 UC + PSC patients were identified and 520 and 212 respectively had complete clinical and endoscopic medical records and were included in the study. Clinical phenotype was described per the guidelines of the NIDDK Inflammatory Bowel Disease Genetics Consortium. Linear regression, t -test, and one-way ANOVA were used for statistical analysis using the SPSS and SigmaPlot. Results: Colitis severity was significantly lower in UC + PSC compared to UC patients, as assessed by a modified Mayo global assessment score (0.8 versus 2.1, P < 0.01; 0 = quiescent, 1 = mild, 2 = moderate, 3 = severe), including hospitalizations for colitis flare (31% versus 57%, P < 0.01), steroid dependence (10% versus 45%, P < 0.01) and requirement for anti-TNF treatment (12% versus 49%, P < 0.01). UC + PSC patients exhibited a higher incidence of other extra-intestinal manifestations (31% versus 17%, P < 0.01) and episodes of venous thrombosis (15% versus 10%, P = 0.05). There was a reduced colectomy rate in UC + PSC patients (27% versus 49%, P < 0.01) driven by distinct indications, including disease activity (9% versus 43%, P < 0.01) and dysplasia (18% versus 6%, P < 0.01). UC + PSC patients, compared to UC without PSC, exhibited more frequently pancolitis (91% versus 48%) and ileitis (48% versus 13%). Importantly, UC + PSC versus UC patients had higher incidence of dysplasia (43% versus 14% P < 0.001) and CRC (9.7% versus 3.0% P < 0.001), located primarily in the right colon (38% versus 26%, P = 0.04) or in multiple areas (34% versus 18%, P < 0.01). Mortality was higher in UC + PSC compared to UC patients (15.1% versus 0.9%, 19 versus 1 per 1000/year, P < 0.001) and was attributed to colon cancer (4.7%), cholangiocarcinoma (4.3%), and end stage liver disease (4.7%). Conclusions: UC + PSC patients compared to UC patients have significantly milder colitis yet exhibit dramatically higher rates of dysplasia and overall mortality. CRC causes one-third of the deaths in UC + PSC patients, suggesting a need for improved CRC screening in this population. We are currently investigating genetic susceptibility loci and the role of differential gene expression in the unique colitis phenotype in UC patients with PSC.